Registration of 'CP 09‐1430' Sugarcane. Issue 3 (23rd August 2018) - Gordon, Vanessa S.; Sandhu, Hardev S.; McCord, Per; Zhao, Duli; Comstock, Jack C.; Singh, Maninder P.; Davidson, R. Wayne; Sood, Sushma; Baltazar, Miguel; McCorkle, Katherine
Abstract : 'CP 09‐1430' (Reg. No. CV‐178; PI 686940) sugarcane (a complex hybrid of Saccharum spp.) was developed and released (6 June 2016) through cooperative research conducted by the USDA–ARS Sugarcane Field Station, Canal Point, the University of Florida, and the Florida Sugarcane League, Inc., for use on organic muck soils. The clone results from CP cross #06‐0576 (CPCL 00‐6756 × CP 01‐2390) and possesses the following agronomic traits: high cane and sucrose yields, high economic index, and acceptable commercial recoverable sucrose on muck soils. It germinates well, particularly under wet planting conditions. Results of replicated trials on muck soils (2012, five locations; 2013, two locations) included 19 total harvests for the three crop stages. Yield comparisons with check cultivars ('CP 72‐2086', 'CP 78‐1628', and 'CP 89‐2143') indicated CP 09‐1430 had significantly higher means than CP 89‐2143 ( P = 0.10) for the following: stalk weight (1.38 kg stalk −1 ), second ratoon cane yield (129.4 Mg ha −1 ), mean cane yield of three crops (146.4 Mg ha −1 ), sugar yield (plant cane [21.9 Mg ha −1 ], second ratoon [13.1 Mg ha −1 ], and overall mean for the three crop harvests [17.6 Mg ha −1 ]); and the economic index (US$3137 ha −1 ). CP 09‐1430 is susceptible to brown rust, scald, and ratoon stunting disease and is moderately resistant to orange rust, smut, and Sugarcane yellow leaf virus, with full resistance to mosaic. It is moderately resistant to freezing temperatures.